The epidemiology and burden of respiratory syncytial virus and influenza infections in hospitalized children under 5 years old in Zhejiang, China (2018–2023) - Sun, Wanwan; Duan, Qiuyao; Guo, Lei; Zhu, An; Tang, An; Miao, Ziping; Zhang, Yu; Yuan, Fen; Fu, Xiaofei; Shi, Suyan; Wang, Lan; Li, Shijian; et al. (Frontiers in Public Health, 2025)
ObjectiveEstimate changes in hospital-based respiratory syncytial virus (RSV) disease burden before and after the COVID-19 pandemic and compare this burden with influenza among children younger than 5 years old in China’s Zhejiang Province.MethodsWe enrolled hospitalized children under 5 years old from eight hospitals in Zhejiang Province. Multiple testing methods were used to compare epidemiological characteristics, and multivariate logistic regression analyses were used to estimate the odds ratio (OR) and 95% confidence interval (CI) between the two groups.ResultsIn this study, of the 7,857 RSV and 2,571 influenza patients, the median age of the children was significantly lower for RSV infection than for influenza. Inpatients with RSV had longer hospitalization durations (mean: 5.66 days vs. 5.04 days; p < 0.001) and hospitalization costs (mean: 5,616.12 RMB vs. 5,352.99 RMB; p = 0.023) than those with influenza. RSV inpatients increased from 1,081 before the COVID-19 pandemic to 6,776 after the pandemic (p < 0.001), with 526.8% more hospitalizations than before the pandemic (p < 0.001). During 2020–2023, hospitalized children were older (16.86 months vs. 10.09 months; p < 0.001) and had a higher proportion of pneumonia (82% vs. 75% of hospitalized patients; p < 0.001) than during pre-pandemic seasons for children admitted due to RSV infection. However, the average RSV hospitalization cost was much lower after the pandemic (4,299.29 RMB vs. 5,697.51 RMB; p < 0.001). Compared with the prepandemic years (2018–2019), the influenza groups showed a similar trend; the number of inpatients increased during the 2020–2023 season (1,949 vs. 622, p < 0.001), with older ages (33.13 months vs. 27.42 months, p < 0.001), a lower proportion of pneumonia (38% vs. 45%, p < 0.001), and lower costs (3,631.03 RMB vs. 3,742.59 RMB, p < 0.001). RSV infection was related to a higher risk of hospitalization in all age groups, and the greatest risk was observed in the 6–12 month age group (OR = 23.1; 95% CI, 18.0–29.6), followed by the 5 months and younger group (OR = 22.4; 95% CI, 17.3–28.9), compared with influenza infection.ConclusionRSV is a significant contributor to disease burden in hospitalized children under 5 years old, outweighing influenza. The COVID-19 pandemic impacted the epidemiological characteristics and disease burden of hospitalization for RSV and influenza infections. A more effective prevention strategy for both infections in young children, especially vaccinations against RSV and influenza, is urged.